UPAYA MENINGKATKAN HASIL BELAJAR IPA MELALUI PENGGUNAAN VIDEO PEMBELAJARAN BAGI SISWA KELAS IV DI SDN 187/IV KOTA JAMBI - Juniar Siregar (Jurnal Dinamika Pendidikan, 2015)
This study presents a research report on improving students’ Learning results on IPA through Video. The objective was to find out whether students’ learning result improved when they are taught by using Video. It was conducted using classroom action research method. The subject of the study was the Grade IV students of SDN 187/IV Kota Jambi which is located on Jln. Adi Sucipto RT 05 Kecamatan Jambi Selatan, and the number of the students were 21 persons. The instruments used were test. In analyzing the data, the mean of the students’ score for the on fisrt sycle was 65,4 (42,85%) and the mean on cycle two was 68,5 (37,15%) and the mean of the third cycle was 81,4 (100%). Then it can be concluded that the use of video on learning IPA can improve the students’ learning result. It is suggested that teachers should use video as one of the media to improve students’ learning result on IPA.Keywords : IPA, students’ learning result, video